Effect of ultraviolet aging on dynamic mechanical properties of SBS modified asphalt mortar. (26th April 2021) - Yu, Huanan; Yao, Ding; Qian, Guoping; Cai, Jun; Gong, Xiangbing; Cheng, Lieguang
Highlights: The UV intensity and radiation time equivalent conversion equation were developed. The UV intensity or radiation time could be shifted to reference point to get the equivalent value. The impaction of UV aging on elastic and viscous modulus were different. Damage of asphalt by UV can be characterized into four different stages. Abstract: Many in-door ultraviolet (UV) aging tests have been conducted on the performance of asphalt mixture, however, there is still lack of guidance for the determination of UV intensity and radiation time for proper simulation of field long-term aging. In order to evaluate the UV aging time and intensity equivalent conversion effect on the performance of asphalt mixture, the asphalt mortar of Styrene Butadiene Styrene (SBS) polymer-modified AC-13 asphalt mixture was prepared and molded. The bending modulus, dynamic modulus, and scanning electron microscope (SEM) tests were carried out to evaluate the dynamic mechanical properties and micro-structure morphology characteristics of asphalt mortar after UV aging. Based on the dynamic mechanical analysis (DMA), the equivalent conversion equation were developed for the impact evaluation of the UV intensity and aging time. Results also found that the bending modulus of SBS modified asphalt mortar increased with the increase of UV intensity and aging time. The storage modulus and complex modulus gradually increased with the intense of aging, but the aging impact of loss modulus and loss factor were not obvious. The SEM result clearly showed that the damage such as wrinkles, cracks and pits were developed from the surface layer to the bottom of the asphalt mortar, and which can be characterized by four different stages.